2004
DOI: 10.1007/s00209-003-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic knots spanning accidental Seifert surfaces of arbitrarily high genus

Abstract: A method for constructing hyperbolic knots each of which bounds accidental incompressible Seifert surfaces of arbitrarily high genus is given. (2000): 57N10, 57M25. Mathematics Subject Classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Statement of the theorem. Lyon [Ly71, Theorem 2] showed that there exists a non-fibered knot K of genus one that admits incompressible Seifert surfaces of arbitrarily large genus (see also [Sce67,Gu81,Ts04] for related examples). By the discussion in Section 3, this implies that π(K) splits over free groups of arbitrarily large rank.…”
Section: Note That Inmentioning
confidence: 99%
“…Statement of the theorem. Lyon [Ly71, Theorem 2] showed that there exists a non-fibered knot K of genus one that admits incompressible Seifert surfaces of arbitrarily large genus (see also [Sce67,Gu81,Ts04] for related examples). By the discussion in Section 3, this implies that π(K) splits over free groups of arbitrarily large rank.…”
Section: Note That Inmentioning
confidence: 99%
“…Turning to surfaces with boundary, it is known that all three geometric types occur in hyperbolic link complements. For example, Tsutsumi constructed hyperbolic knots with accidental Seifert surfaces of arbitrarily high genus [25]. On the other hand, Fenley proved that minimal genus Seifert surfaces cannot be accidental [9].…”
Section: Introductionmentioning
confidence: 99%